2002
DOI: 10.1021/jp014512r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Molecular Environment on the Three-Center versus Four-Center Elimination of HBr from Vinyl Bromide: A Theoretical Approach

Abstract: The dynamics of dissociative reactions of vinyl bromide was investigated by Langevin molecular dynamics method in the absence and in the presence of frictional interaction between the molecule and its environment. The results show a redistribution of the vibrational energy on the bonds of vinyl bromide under the effect of frictional interaction. This redistribution can modify the reaction rates of vinyl bromide dissociation channels. Increasing the frictional coupling between vinyl bromide and its environment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In our previous studies we found several cases when the kinetic energy shows inhomogeneous and temperature-dependent distribution on the molecules, which is raised by the solute-solvent interactions [8,9].…”
Section: Resultsmentioning
confidence: 91%
“…In our previous studies we found several cases when the kinetic energy shows inhomogeneous and temperature-dependent distribution on the molecules, which is raised by the solute-solvent interactions [8,9].…”
Section: Resultsmentioning
confidence: 91%
“…Consistent with XRD and TEM results, the XPS spectra of spent catalysts confirm the formation of BaClF during the catalytic pyrolysis of HCFC-142b ( Figure S5). In addition to the composition of catalysts, reaction temperature [40], reaction pressure and environment [41] play an important role in the catalytic performance of the pyrolysis process. These issues will be addressed in the future studies after the optimization of the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent examinations regarding some special reactions of vinyl bromide [17] and of the whole vinyl-halogenid serie [18] pointed out the decisive role of vibrational energy distribution and induced redistribution on the dissociation reaction rate. Therefore, the methodology described there [17,18] was followed to examine the backgrounds of the unexpected reactivity difference of 1, 2 and 3 predicted by the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the methodology described there [17,18] was followed to examine the backgrounds of the unexpected reactivity difference of 1, 2 and 3 predicted by the experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation